The Role of Social Media in Marketing Communication for Santet Segoro Pitu Film - Andriano, Stefanus (Communicare : Journal of Communication Studies, 2025)
The advancement of internet-based communication technologies has significantly transformed the marketing communication landscape, particularly for businesses aiming to boost sales and profitability. In Indonesia, where internet connectivity has markedly increased, social media has emerged as a crucial tool for marketing efforts. This study investigates how Hitmaker Studios uses these platforms to promote the horror film "Santet Segoro Pitu," focusing primarily on Instagram. By employing qualitative methods such as in-depth interviews and direct observations, the research examines the marketing strategies employed by the studios’ team. Initial findings indicate that well-organized social media content management is essential for driving ticket sales. These insights could provide valuable guidance for the effective use of social media in marketing, offering benefits not only within the entertainment industry but also in other areas. Ultimately, this research emphasizes the importance of creatively integrating marketing communication strategies with social media to enhance overall marketing effectiveness.